Facile preparation of a cobalt diamine diketonate adduct as a potential vapor phase precursor for Co3O4films. Issue 30 (20th July 2021) - Klotzsche, Max; Barreca, Davide; Bigiani, Lorenzo; Seraglia, Roberta; Gasparotto, Alberto; Vanin, Laura; Jandl, Christian; Pöthig, Alexander; Roverso, Marco; Bogialli, Sara; Tabacchi, Gloria; Fois, Ettore; et al.
Abstract : A novel heteroleptic Co(ii ) complex has been synthesized, characterized and successfully evaluated as a precursor for the CVD of Co3 O4 thin films with tailored properties. Abstract : Co3 O4 thin films and nanosystems are implemented in a broad range of functional systems, including gas sensors, (photo)catalysts, and electrochemical devices for energy applications. In this regard, chemical vapor deposition (CVD) is a promising route for the fabrication of high-quality films in which the precursor choice plays a key role in the process development. In this work, a heteroleptic cobalt complex bearing fluorinated diketonate ligands along with a diamine moiety [Co(tfa)2 ·TMEDA; tfa = 1, 1, 1-trifluoro-2, 4-pentanedionate and TMEDA = N, N, N ′, N ′-tetramethylethylenediamine] is investigated as a potential Co molecular precursor for the CVD of Co3 O4 systems. For the first time, the compound is characterized by crystal structure determination and comprehensive analytical studies, focusing also on its thermal properties and fragmentation patterns, important figures of merit for a CVD precursor. The outcomes of this investigation, accompanied by detailed theoretical studies, highlight its very favorable properties for CVD applications. In fact, growth experiments under oxygen atmospheres containing water vapor revealed the suitability of Co(tfa)2 ·TMEDA for the fabrication of high-quality, phase-pure Co3 O4 thin films. The versatility of the proposed strategy in tailoring Co3 O4 structural/morphological features highlights its potential to obtain multi-functional films with controllable properties for a variety of eventual technological end-uses.